Co(II) Complex of Mefloquine Hydrochloride: Synthesis, Antimicrobial Potential, Antimalaria and Toxicological Activities - Adediji J. Femi; Obaleye J. Ayoola (E-Journal of Chemistry)
Transition metal complex of Co(II) with Mefloquine hydrochloride (antimalaria drug) was synthesized using template method. Chemical analysis including conductivity measurements and spectroscopic studies were used to propose the geometry and mode of binding of the ligand to metal ion. From analytical data, the stoichiometry of the complex has been found to be 1:1. Infrared spectral data also suggest that the ligand (mefloquine hydrochloride) behaves as a tridentate ligand with N:N:O donor sequence towards the metal ion. The complex generally showed octahedral coordinate geometry. Conductivity measurement of 10-2 mol dm-3 methanol solution of the complex indicated non-electrolytic nature of metal complex. It also revealed that the ligand anions were covalently bonded to the complex. In-vivo evaluation of antimicrobial studies of the metal complex showed greater activities when compared to the free mefloquine.The complex was screened against malarial parasites (Plasmodium yoelii nigeriensis): It was evident from the results obtained that Co(II) mefloquine has highest clearance of about 80% parasitaemia reduction compared to the free mefloquine. The ligand and metal complex were screened for their toxicological activities at the dose of 0.60 mg/Kg body weight twice daily for seven days on the alkaline phosphatase (ALP), alanine aminotranferase (ALT), and aspartate aminotransferase (AST) activities of rat serum, liver and kidney. Overall, it was revealed that both mefloquine and its metal complex do not showed toxicity particularly on the liver and kidney.